PRINCIPLES OF INNOVATIVE EDUCATION THROUGH THE PRISM OF A SYSTEM APPROACH - Olena Tadeush Borys Grinchenko Kyiv University (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article considers the theoretical and practical importance of using general scientific methodology and, in particular, a systematic approach as a methodological basis for understanding the essence of innovative education and the ability to identify, structure and organize the body of knowledge about all its components. It is noted that innovations in education should be focused primarily on the spiritual, human nature of innovative transformations, cultural and professional development of students, stimulate creative thinking, form a spiritual value system, willingness to make decisions and be responsible for them in constant change, risk, innovation. The concept of «principles of innovative education» as a starting point of a systemic nature aimed at improving the quality of innovative education, in particular, improved or new educational systems, components of the educational process, educational technologies, scientific and methodological developments, technical means of educational institutions. The content of the principles of innovative education is defined, substantiated and characterized through the prism of a systems approach: the principle of global goal, the principle of integrity, the principle of structure, the principle of hierarchy, the principle of functionality, the principle of functionality, uncertainty. The study of certain principles of innovative education in the perspective of a systems approach shows that their implementation in the modern educational space will ensure the integrity of transformations of innovative education and integrative outcome, which will significantly exceed significant changes in individual components of its system.